Ambient Conditioned, Solution Processed CuO Nanoflakes over Carbon Fabric for Supercapacitor Application: Performance Enhancement via Nanoparticle Attachment - Pal, Shreyasi; Maiti, S.; Dutta, S.; Chattopadhyay, K. K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
All Solid-state supercapacitors based on pure CuO nanoflakes and CuO@Au heterostructure over carbon cloth were fabricated where directly functioned nanostructure over carbon fiber acts as electrode and detour the necessity of any binder or ancillary materials. High coverage of CuO nanoflakes over entire cylindrical surface of each fiber provide decent electrochemical which nwas further uplifted after Au nanoparticle decoration. Registered electrochemical performance from CuO nanoflakes was found to be 11 F/g at current density 0.5A/g which significantly improved to 26 F/g at the same current density after nanoparticle attachment. Increase in surface area as well as increment of overall conductivity of the hybrid system due to Au nanoparticle attachment may accredit for such performance enrichment. All Solid-state supercapacitors based on pure CuO nanoflakes and CuO@Au heterostructure over carbon cloth were fabricated where directly functioned nanostructure over carbon fib eracts as electrode and detour the necessity of any binder or ancillary materials. High coverage of CuO nanoflakes over entire cylindrical surface of each fiber provide decent electrochemical which was further uplifted after Au nanoparticle decoration. Registered electrochemical performance from CuO nanoflakes was found to be 11 F/g at current density0.5A/g which significantly improved to 26 F/g at the same current density after nanoparticle attachment. Increase in surface area as well as increment of overall conductivity of the hybrid system due to Au nanoparticle attachment may accredit for such performance enrichment.